Analisis Multi-Geohazard dengan Metode Multi-Criteria Decision Analysis di Kawasan Ibu Kota Nusantara (IKN), Kalimantan Timur, Indonesia - Naufal, Muhammad Adi; Bayuaji, Giri; Absari, Hirundini Rustica; Kurniawan, Fathoni Tri (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2024)
The relocation capital city of Indonesia from Jakarta to the Nusantara Capital City is in North Penajam Paser Regency (Sepaku District) and Kutai Kartanegara (Samboja District and parts of Loa Kulu, Loa Janan and Muara Jawa Districts), East Kalimantan Province. The emergence of new centers of activity in the region led to increased vulnerability to geological hazards. Analysis of potential geological hazards is important to identify areas that have a high risk of these threats. This study combines the concept of